Work and pay in flexible and regulated labor markets: A generalized perspective on institutional evolution and inequality trends in Europe and the US - Thomas A. DiPrete; Dominique Goux; Eric Maurin; Amélie Quesnel-Vallée (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2003)
In den letzten Jahren hat sich eine unified theory aus der Arbeitsökonomik heraus-gebildet, in der die Meinung vorherrscht, dass die Kombination makroökonomi- scher Schocks und flexibler Arbeitsmarktinstitutionen in den USA eine starke Zu-nahme der Lohnungleichheit verursacht habe, während die gleichen Schocks in Europa vor allem für gering qualifizierte Arbeitnehmer eine hohe Arbeitslosigkeit und geringe Beschäftigungsniveaus gebracht hätten als (unerwünschter) Nebeneffekt der durch die strikten institutionellen Regelungen des Arbeitsmarkts in Europa rigiden Löhne. In der vorliegenden Analyse wird hingegen argumentiert, dass Institutionen in Europa eigene Formen der Flexibilität entwickelt hätten, die - im Gefolge der in der unified theory beschriebenen Schocks - ebenfalls zu einer zunehmenden Un-gleichheit in Europa geführt hätten, aber eben in anderer Gestalt. In Frankreich sei beispielsweise die Ungleichheit bei der Arbeitsplatzsicherheit schneller gewachsen als in den USA. Darüber hinaus hätten Entwicklungen auf dem französischen Ar-beitsmarkt dazu geführt, dass sich gering qualifizierte Arbeitnehmer in unsicheren Beschäftigungsverhältnissen konzentrierten. – – In recent years a 'unified theory' has emerged out of labor economics, which argues that a combination of 'macroeconomic shocks' and flexible labor market institutions in the U.S. has produced strong upward trends in wage inequality, while these same shocks have produced high unemployment and low employment growth in Europe as a side effect of the wage stability preserved by that continent's rigid labor market in-stitutions. This paper argues instead that European institutions in fact have evolved their own form of flexibility, which, in combination with the macroeconomic shocks described in the unified theory, have also led to rising inequality in Europe, but of a different form. Taking France as an example, inequality of employment security has risen faster here than in the U.S. Furthermore, trends in the French labor market have led to increased concentration of low-skill workers in these insecure job statuses. These results challenge the view that unemployment is the main mecha-nism through which European labor markets absorbed asymmetric shocks to their demand for labor. They also challenge the view that Europeans have intolerance for inequality, but instead suggest that the main difference between the two sides of the Atlantic concerns the nature of the inequalities that each society is willing to tolerate.
Keywords: 330; Arbeitsmarktflexibilisierung; Institutioneller Wandel; Schock; Lohnstruktur; Arbeitslosigkeit; Arbeitsplatzsicherung; Risiko; Vergleich; USA; Frankreich